LITERASI KEUANGAN, PENGETAHUAN INVESTASI, MOTIVASI INVESTASI, DAN PERSEPSI RETURN PENGARUHNYA TERHADAP MINAT INVESTASI MAHASISWA (Studi Mahasiswa S1 FEB Universitas di Purwokerto: Universitas muhammadiyah Purwokerto dan Universitas Jenderal Soedirman Angkatan 2018-2020) - Akhmad Darmawan; Amy Anjelina; Fatmah Bagis (Jurnal Akuntansi dan Pajak, 2023)
This study aims to analyze the effect of financial literacy, effect of investment, investment motivation, and return perception on student investment interest. The type of study is quantitative research. The sample selection in this study used a purposive sampling technique and the primary data obtained in this study using a questionnnaire with 333 respondents. The results of the analysis show that financial literacy, effect of investment, investment motivation, and return perception simultaneously has a significant effect on investment interest. Meanwhile, financial literacy, effect of investment, investment motivation, and return perception partially significant effect on investment interest. Keywords : Financial Literacy, Effect Of Investment, Investment Motivation, Return Perception, And Investment Interest.